Prevalence of a first-degree relative with colorectal cancer and uptake of screening among persons 40 to 54 years old - Weigl, Korbinian; Tikk, Kaja; Hoffmeister, Michael; Kolligs, Frank Thomas; Schweigler, Dirk; Brenner, Hermann (Clinical gastroenterology and hepatology, 2020)
Background & Aims - People with a first-degree relative with colorectal cancer (CRC) are recommended to start CRC screening at age 40. However, there is limited information on how many people in different age groups have a known family history of CRC and how many of them have had a colonoscopy. - Methods - We set up a multicenter, cross-sectional, population-based study in Germany to determine what proportions of persons in age groups from 40 to 54 years old have a known family history of CRC. We invited 160,000 persons to participate in an online survey from 2015 through 2016. We investigated what proportions of persons in each age group reported a family history of CRC and what proportions of persons underwent a colonoscopy examination using descriptive statistics and multiple logistic regression models. - Results - Of 28,711 responders to the online questionnaire (8428 were age 40-44 years, 9879 were age 45-49 years, and 10,404 were age 50-54 years), 2705 stated that they had a first-degree relative with CRC (9.4%). The prevalence of a first-degree relative with CRC increased with age: 7.5%, 9.6%, and 10.9% for people 40 to 44 years old, 45 to 49 years old, and 50 to 54 years old, respectively. The prevalence of a first-degree relative who received a diagnosis of CRC at age 70 years or older increased steadily with each age group. Although a greater proportion of people with a family history of CRC had undergone a colonoscopy examination (54.5%) than people without a family history of CRC (25.7%; P < .0001), large proportions of people within this risk group were not in compliance with the guidelines (54.8%, 47.6%, and 38.6% for ages 40-44 y, 45-49 y, and 50-54 y, respectively). - Conclusions - One in 10 persons in Germany age 40 to 54 years old has a first-degree relative with CRC. Guidelines recommend initiation of screening at ages 40 to 45 years for people with a family history, yet at this age many people do not have a family history of CRC yet, and almost half of persons 40 to 54 years old with a family history of CRC have not yet received a screening colonoscopy.
Available online 4 December 2019
Gesehen am 26.10.2021